Bishop Files : Final Shadows - Book 3 - Hooper, Kay (Thorndike, Maine : Center Point Large Print, 2019)
"A desperate underground war with the survival of millions at stake looms in the electrifying conclusion of the New York Times bestselling Bishop Files Trilogy"--
Keywords: Suspense fiction